Anaerobic digestion of fique bagasse: an energy alternative (2014)
In Colombia the agro-industrial process of fique generates approximately 20 800 kg of waste / ha planted, consisting of bagasse and juice. These wastes are discarded over soil and water generating a problem of environmental pollution. The fique bagasse (FB) has a calorific value of 3 297.91 kcal / kg, high concentrations of cellulose, hemicellulose and C / N ratio that make it appropriate for biogas production. However, the presence of lignin in the FB requires specific microbial consortia for its degradation. Therefore, in this research the biogas production from FB on a laboratory scale was studied through the Anaerobic Digestion (AD) process using a consortium of ruminal fluid (RF) and pig manure (PM). A methane production of 0.35 m3 CH4/kg volatile solids (VS) added during two weeks, equivalent to 1.38 kWh/kg VS added, indicated that FB is an attractive residual to be used as a source of renewable energy.